Drug-induced arterial hypertension in a patient with ischemic stroke - G. R. Ramazanov; E. V. Shevchenko; R. Sh. Muslimov; I. S. Aliev (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
Progressive ischemic stroke is the most frequent form of stroke with neurologic deterioration. The pathogenesis of progressive ischemic stroke is based on the expansion of the brain infarction zone and reduction of the "penumbra" zone in the area of focal ischemia. The leading role in maintaining the balance between irreversible and reversible ischemia belongs to cerebral collateral blood flow. Being a multifactorial phenomenon, collateral blood flow is caused by both morphological and functional characteristics of the collateral arterial channel and systemic factors, among which hemodynamics is of great importance. The tactic of purposeful increase in blood pressure to improve cerebral perfusion is called drug-induced arterial hypertension. A number of experimental studies have demonstrated the safety and efficacy of this method, but the small number and heterogeneity of data in the studies do not allow us to conduct a meta-analysis and form an optimal protocol for drug-induced arterial hypertension. In this article we want to describe the clinical observation of a patient with ischemic stroke on the background of critical stenosis of stroke-related internal carotid artery and atrial fibrillation, in the treatment of which we applied drug-induced arterial hypertension.